(untitled) (African Journal of Public Administration & Management, 2026)
The benefits of participation and inclusion must be not only clarified in the strategies and plans of participatory governance but also realized in form of well-being they generate. Integrated leadership needs to be placed at different levels of governance and in the society so that participation and inclusion permeate through public governance not as a gimmick but as a highly cherished and beneficial governance value. Participation and inclusion must be comprehensively conceptualized and practiced to include participation in priority setting, planning, production of services and good, paying for services and goods, consumption and well-being to avoid frustrating and exploitative participation. People need to be sensitized and even skilled in this kind of comprehensive participation and inclusion. They need to have a mindset and attitude that internalize that their development and well-being can only be achieved through their own participation and engagement as well as in holding their leadership and themselves accountable In the design and operation of accountability systems and structures, accountability must be broken down into the various accountabilities to ensure non ambiguity which makes people pay attention only to financial accountability. All this needs to be promoted through integrated visionary and transformational leadership at every level of governance and in all sectors.